Cancer‐related fatigue in breast cancer patients after surgery: a multicomponent model using partial least squares—path modeling. Issue 4 (22nd October 2013) - Bortolon, Catherine; Krikorian, Alicia; Carayol, Marion; Brouillet, Denis; Romieu, Gilles; Ninot, Gregory
Abstract Objective The aim of this study is to examine factors contributing to cancer‐related fatigue (CRF) in breast cancer patients who have undergone surgery. Methods Sixty women (mean age: 50.0) completed self‐rated questionnaires assessing components of CRF, muscular and cognitive functions. Also, physiological and subjective data were gathered. Data were analyzed using partial least squares variance‐based structural equation modeling in order to examine factors contributing to CRF after breast surgery. Results The tested model was robust in terms of its measurement quality (reliability and validity). According to the structural model results, emotional distress (β = 0.59; p < 0.001), pain (β = 0.23; p < 0.05), and altered vigilance (β = 0.30; p < 0.05) were associated with CRF, accounting for 61% of the explained variance. Also, emotional distress (β = 0.41; p < 0.05) and pain (β = 0.40; p < 0.05) were related to low physical function and accounted for 41% of the explained variance. However, the relationship between low physical function and CRF was weak and nonsignificant (β = 0.01; p > 0.05). Conclusion Emotional distress, altered vigilance capacity, and pain are associated with CRF in postsurgical breast cancer. In addition, emotional distress and pain are related to diminished physical function, which, in turn, has no significant impact on CRF. The current model should be examined in subsequent phases of the treatment (chemotherapy and/or radiotherapy) when side effects are more pronounced and may lead to increased intensity of CRF and low physical function. Copyright © 2013 John Wiley & Sons, Ltd.